Abscopal responses in patients with metastatic melanoma involving skin and subcutaneous tissues treated with intralesional IL2 plus BCG - Vidovic, Dejan; Helyer, Lucy Kathryn; Pasternak, Sylvia; Giacomantonio, Carman Anthony (Frontiers in Oncology, 2023)
Cutaneous melanoma is relatively common with increasing incidence and significant mortality. While the mainstay of therapy is surgical, patients with stage III and IV disease fare poorer than those with early-stage disease and often benefit from adjuvant therapies. While systemic immunotherapy has changed the landscape of melanoma treatment, for some patients systemic toxicities related to these treatments prohibit successful administration or completion of therapy. Moreover, it is becoming increasingly evident that nodal, regional, and in-transit disease appears to be resistant to systemic immunotherapy relative to responses observed in distant metastatic disease sites. In this scenario, intralesional immunotherapies may offer benefit. In this case series, we describe the use of intralesional IL-2 and BCG at our institution in ten patients with in-transit plus or minus distant cutaneous metastatic melanoma over the last twelve years. All patients received intralesional IL2 and BCG. Both treatments were very well tolerated with only grade 1/2 adverse events. In our cohort, complete clinical response was 60% (6/10), progressive disease in 20% (2/10), and no response in 20% (2/10) of patients. The overall response rate (ORR) was 70%. The median overall survival was 35.5 months and mean overall survival 43 months in this cohort. Herein we further highlight the clinical, histopathological, and radiological course of two complete responders, showing evidence of an abscopal effect with resolution of distant untreated metastasis. Together, this limited data supports the safe and effective use of intralesional IL2 and BCG for the treatment of metastatic or in-transit melanoma in this challenging patient cohort. To our knowledge, this is the first formal study to report on this combination therapy for the treatment of melanoma.